(3cJGH aj CUhd GdCLSGe heG jJYdb HgGs - (3Ydj Hf eMeO Hf Ydj, CHh GdMSf GdWHQj, GdedbH HYeGO GdOjf, GdeYQha HGdcjG GdgQGSj,J (B504 (3g` s ((3CjhH Hf YKeGf s)
(3ChdgG (B:s
(3HYO GdHSedI hGdMeO dg bGd GdcjG GHh GdMSf GdLjdj LeYJ aj gPG GdcJGH ef CUhd UfGYI GdCLSGe hMedJgG GdWQjb Edi GdJUQa ajgG hGSJYeGdgG deG XffJg cGajkG ai eYfGg s
(3BNQgG (B:s
(3aEPG MVQfG CeQ ef GdCehQ GdeJYdbI HGdUfGYI CMSHfG GdfXQ ajg hejRfG Hjf GdeSYhO hGdefMhS hHjf Gdbhj hGdVYja hbGHdfG GdTgGOGJ GdeMehOI hGdePeheI HYVgG HHYV MJi fdNU ef GdHjf CZdHgG s
(3Vef eLehY , JQJjHgG (B: 8s
(3bQf GdfSN (B:s
(3GdbQf GdYGTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B329 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B7 - (3U (B220s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG EWGQGJ s
Keywords: (3eJaQbGJs